Stabilization of road embankment using expanded polystyrene (EPS) geofoam - Muhammad Abdul Rabbani Bin Ja'apar (School of Environmental Engineering, University Malaysia Perlis, 2014)
This report presents the results for settlement and factor of safety (FOS) of road embankment. In this report also shows analyze the comparison road embankment has Expanded Polystyrene (EPS) Geofoam and without Expanded Polystyrene (EPS) Geofoam. The finite element method (FEM) using PLAXIS 2D software has been used to calculate the settlement and factor of safety of road embankment.